SOFTNESS AND KUNG FU: Masculinities of Chinese Heroes in American Graphic Novels. - Lian, Xu (Kritika Kultura, 2026)
In American graphic novels such as Avatar: The Last Airbender, The Shadow Hero, and Kung Fu Panda, the depictions of Chinese heroes differ from those of Western heroic characters in mainstream American graphic narratives. These heroes embody a combination of soft masculinity and kung fu masculinity, creating a new type that might be called the "soft kung fu hero," exemplifying what Kam Louie refers to as "wen wu shuang quan" (accomplished in both cultural attainment and martial prowess)—the ultimate ideal of Chinese masculinity. Although the appearances of the protagonists are quite different from typical kung fu masculine heroes such as Bruce Lee and Shang-Chi, the martial abilities of these heroes nonetheless draw on elements of kung fu. The soft masculinity type of Chinese heroes in American graphic novels is not only a result of the influence of Chinese culture and caizi stories that deemphasize the physical dimension and highlight peace as well as spiritual cultivation, but is also the result of Western stereotypes and ideological impulse to treat China as the Other. The soft masculinity challenges the binary gender norms in American society by queering the protagonists as effeminate characters. Meanwhile, representation of kung fu masculinity in graphic narratives is influenced by kung fu films and television, especially those by Bruce Lee; this type is closer to the norms of Western hegemonic masculinity, but removes the aggressive and belligerent side of the latter. The fusion of these two in the heroic images of characters such as Aang and the Shadow Hero is not a simple combination, but involves a process of reorganization and transformation of its constituent elements.